The Effect of Tax Socialization and Tax Rates to Restaurant Taxpayable Compliance in The City of Sukabumi - Irsan Permana; Triendar Susianto (LPPM Sekolah Tinggi Ilmu Ekonomi PGRI Sukabumi, 2020)
This study aims to determine the tax socialization, tax rates, tax compliance, the influence of tax socialization on tax compliance, the influence of tax rates on tax compliance, and the effect of tax socialization and tax rates on restaurant taxpayer compliance in Sukabumi City. The research method uses quantitative methods with descriptive-associative methods. The unit of analysis used is restaurants in Sukabumi City, with the population used are all restaurants in Sukabumi City, and the total sample size of 70 respondents. Data collection techniques in the form of a questionnaire containing 19 indicator statements and determined by the simple random sampling method. Analysis of the data used is the instrument test, classic assumption test, descriptive analysis, multiple correlation analysis, coefficient of determination analysis, multiple linear regression analysis, and t test (partial test) and F test (simultaneous test). The results of this study indicate that; 1) tax socialization based on restaurant respondents' responses shows that on the whole the overall response was agreed with the tax socialization conducted towards restaurants in Sukabumi City. 2) tax rates based on respondents' responses indicate that on average the overall response was neutral with the imposition of tax rates on restaurants in the City of Sukabumi. 3) taxpayer compliance based on respondents' responses shows that on average the overall respondent agreed to the compliance of restaurant taxpayers in Sukabumi City, in the sense that respondents were compliant with the existence of taxpayers to their respective restaurants. 4) tax socialization has a positive and significant effect on restaurant taxpayer compliance in Sukabumi City. 5) tax rates have a positive and significant effect on restaurant taxpayer compliance in Sukabumi City. 6) tax socialization and tax rates have a positive and significant effect on restaurant taxpayer compliance in Sukabumi City.